Self-Experienced Trunk Appearance in Individuals With and Without Idiopathic Scoliosis. Issue 8 (15th April 2020) - Savvides, Panayiotis; Gerdhem, Paul; Grauers, Anna; Danielsson, Aina; Diarbakerli, Elias
Abstract : Study Design: Cross-sectional. Objective: The aim of this study was to describe the self-experienced trunk appearance in individuals with and without idiopathic scoliosis. Summary of Background Data: Idiopathic scoliosis is the most common spinal deformity. A large scoliotic deformity increases the risk of back pain and pulmonary dysfunction. The deformity has also a psychological impact. Methods: The pictorial part of the spinal appearance questionnaire (pSAQ) was administered to 1416 individuals with idiopathic scoliosis (386 untreated, 529 brace treated, 501 surgically treated) and 272 individuals without scoliosis from the general population. Comparisons were made between individuals with and without scoliosis, between treatment groups and sex in the scoliosis group. Results: Mean (95% confidence interval) age of the individuals with scoliosis was 36.2 (35.5–36.9) years and for the individuals without scoliosis 40.2 (37.9–42.4). pSAQ total was 12.3 (12.1–12.5) for individuals with scoliosis and 7.4 (7.3–7.6) for individuals without scoliosis ( P < 0.001, adjusted for age and sex). pSAQ total was 11.5 (11.1–11.9) for untreated, 13.0 (12.6–13.3) for brace treated, and 12.3 (11.9–12.6) for surgically treated individuals ( P < 0.001, adjusted for sex and curve size). The pSAQ total between males and females with idiopathic scoliosis did not differ ( P = 0.22 adjusted for age and curve size). Conclusion: This study shows that individuals with idiopathic scoliosis have more concern about their body appearance than individuals without scoliosis. Untreated individuals are not as bothered of their spinal appearance as treated individuals. Males and females with scoliosis do not differ significantly in the perception of their spinal appearance. Level of Evidence: 3 Abstract : This study of 1416 individuals with idiopathic scoliosis and 272 individuals without idiopathic scoliosis showed that scoliosis negatively affects the perceived spinal appearance.